Pathological changes in hippocampal neuronal circuits underlie age-associated neurodegeneration and memory loss: Positive clue toward SAD. (20th August 2015) - Moorthi, P.; Premkumar, P.; Priyanka, R.; Jayachandran, K.S.; Anusuyadevi, M.
Highlights: Learning and memory deficit observed due to sequential neurodegeneration during aging. Pathological changes in neuronal networks found as a clear clue for spreading pathology. Resveratrol proved efficacious in diminishing pathological events during aging. Abstract: Among vertebrates hippocampus forms the major component of the brain in consolidating information from short-term memory to long-term memory. Aging is considered as the major risk factor for memory impairment in sporadic Alzheimer's disease (SAD) like pathology. Present study thus aims at investigating whether age-specific degeneration of neuronal-circuits in hippocampal formation (neural-layout of Subiculum-hippocampus proper-dentate gyrus (DG)-entorhinal cortex (EC)) results in cognitive impairment. Furthermore, the neuroprotective effect of Resveratrol (RSV) was attempted to study in the formation of hippocampal neuronal-circuits. Radial-Arm-Maze was conducted to evaluate hippocampal-dependent spatial and learning memory in control and experimental rats. Nissl staining of frontal cortex (FC), subiculum, hippocampal-proper (CA1→CA2→CA3→CA4), DG, amygdala, cerebellum, thalamus, hypothalamus, layers of temporal and parietal lobe of the neocortex were examined for pathological changes in young and aged wistar rats, with and without RSV. Hippocampal trisynaptic circuit (EC layerII→DG→CA3→CA1) forming new memory and monosynaptic circuit (EC→CA1) that strengthen old memories were found disturbed in aged rats. Loss of Granular neuron observed in DG and polymorphic cells of CA4 can lead to decreased mossy fibers disturbing neural-transmission (CA4→CA3) in perforant pathway. Further, intensity of nissl granules (stratum lacunosum moleculare (SLM)-SR-SO) of CA3 pyramidal neurons was decreased, disturbing the communication in schaffer collaterals (CA3-CA1) during aging. We also noticed disarranged neuronal cell layer in Subiculum (presubiculum (PrS)-parasubiculum (PaS)), interfering output from hippocampus to prefrontal cortex (PFC), EC, hypothalamus, and amygdala that may result in interruption of thought processes. We conclude from our observations that poor memory performance of aged rats as evidenced through radial arm maze (RAM) analysis was due to the defect in neuronal-circuits of hippocampus (DG-CA4-CA1-Sub) that were significantly damaged leading to memory impairment. Interestingly, RSV was observed to culminate pathological events in the hippocampal neuronal circuit during aging, proving them as potent therapeutic drug against age-associated neurodegeneration and memory loss.